2023
DOI: 10.1093/europace/euad055
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying a spectrum of clinical response in atrial tachyarrhythmias using spatiotemporal synchronization of electrograms

Abstract: Aims There is a clinical spectrum for atrial tachyarrhythmias wherein most patients with atrial tachycardia (AT) and some with atrial fibrillation (AF) respond to ablation, while others do not. It is undefined if this clinical spectrum has pathophysiological signatures. This study aims to test the hypothesis that the size of spatial regions showing repetitive synchronized electrogram (EGM) shapes over time reveals a spectrum from AT, to AF patients who respond acutely to ablation, to AF patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
(35 reference statements)
2
4
0
Order By: Relevance
“…The authors are to be commended for providing a potential solution for processing electrophysiological activation data of AF with the potential to include this information into the ablation procedure. Furthermore, the data of this study reinforce the paradigm that AF perpetuation follows an organized and repetitive activation pattern (10).…”
supporting
confidence: 84%
“…The authors are to be commended for providing a potential solution for processing electrophysiological activation data of AF with the potential to include this information into the ablation procedure. Furthermore, the data of this study reinforce the paradigm that AF perpetuation follows an organized and repetitive activation pattern (10).…”
supporting
confidence: 84%
“…The authors are to be commended for providing a potential solution for processing electrophysiological activation data of AF with the capability to include this information in the ablation procedure. Furthermore, the data of this study reinforce the paradigm that AF perpetuation follows an organized and repetitive activation pattern 10 …”
supporting
confidence: 84%
“…Furthermore, major works have been recently proposed to understand and characterise the organisation of wavefront propagation based on intracardiac recordings. In particular, the study by Ganesan et al [40] defines a novel metric coined as REACT to evaluate the size of the areas containing synchronised EGMs, shown to be predictive of ablation outcomes. Shortly afterwards, a similar analysis proposes Repetitive Atrial Activation Patterns (RAAPs), found to be associated with arrhythmia drivers [41] .…”
Section: Discussionmentioning
confidence: 99%